Effectiveness of live aerobic exercises and video based aerobic exercises on stress reduction among the patients of substance use disorder in de-addiction centre of selected hospitals of Ambala, Haryana - Sonia; Sarin, Jyoti; Garg, Dhanesh (International Journal Of Community Medicine And Public Health, 2025)
Background: Substance use is a major public health concern across the globe. There is a strong link between stress and substance abuse. Everyone copes with stress in different ways, but some people may resort to using drugs or alcohol to manage their stress. The study aimed to assess the effectiveness of live aerobic exercises (LAE) and video based aerobic exercises (VBAE) on stress reduction among the patients of substance use disorder in de-addiction centre of selected hospitals of Ambala, Haryana. Methods: Quantitative research approach, quasi experimental non-equivalent control group pretest post-test design was used to collect the data from 40 patients of substance use disorder (20 LAE group, 20 VBAE group) by using purposive sampling technique. Data was collected by using modified perceived stress scale (PSS-10) through interview technique. Live aerobic exercises and video based aerobic exercises were administered continuously for one week after pretest. Results: The findings showed that there was significant difference in the mean score of stress in live aerobic exercise group and video based aerobic exercise group after administration of live aerobic exercises and video based aerobic exercises as the calculated ‘t’ value was (-5.38 and p=0.001) with mean difference -5.35 which was statistically significant at 0.05 level of significance. Conclusions: Both live aerobic exercises and video based aerobic exercises were effective in reducing the stress among patients of substance use disorder. However, live aerobic exercises were more effective than video based aerobic exercises in stress reduction among patients of substance use disorder.